Negotiation impact in Supply Chain Management - Elena-Simona Ionel (Romanian Economic Journal)
Negotiation is a key factor influencing supply chain management, as it is a critical competency that is directly impacting long term strategic success and operational performance. It is determining critical decisions like supplier selection, contract terms, pricing, warranty, liability and dispute resolution becoming key activity in aligning with stakeholders objectives and mitigating risks in complex global markets. The aim of this paper is to explore the multitude of impacts that negotiation has on supply chain performance, with a focus on cost optimisation, operational resilience and supplier relationship management. Using qualitative research method through an analysis of recent qualitative and quantitative research, including meta-analysis and case studies, the author identifies negotiation as a strategic leverage that increases supply chain reactivity and efficiency. Research hypothesis one is that engaging in effective negotiation practices drives both financial savings and increase collaboration and trust within the supply chain, advocating for accountability and stability even in volatile market conditions. Second research hypothesis states that strategic negotiation allows organizations to foresee and react to diverse challenges such as supply disruptions, inflation, price volatility, demand variation and quality issues by acting with precision and agility, without jeopardising the relationship with different stakeholders. The results and findings confirm the two research hypothesis and highlight the importance of implementing a structured approach in negotiation, focusing significant efforts on preparation, adaptability and mutual value creation. Literature review conducted underscores a series of tools that can be used to enhance the outcome of negotiation, while data analytics, scenario planning, cultural specificities and dedicated training to support continuous improvement of negotiation skills of supply chain professionals are most impactful as studied in more than ten years experience of the author’s practical supply chain negotiation. This study brings additional value to the research field as it is synthesising key findings in academic research and industry practices with a goal to raise awareness and provide guidance to supply chain proffesionalls about the role of negotiation in improving supply chain efficiency offering practical recommendations on how to integrate negotiation as a central component of supply chain strategy. The findings offer supply chain managers the knowledge and tools to beneficiate from the full potential of negotiation, therefore driving sustainable growths and competitive advantage.